Efektifitas Model Pelatihan Outbound Resolusi Konflik dalam Meningkatkan Kemampuan Resolusi Konflik Interpersonal pada Diri Remaja - Ramadhani, Hetti Sari (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
This study aimed to test the effectiveness of the model outbound conflict resolution training to improve interpersonal conflict resolution skills in adolescent self . The population was 198 adolescents aged 16-18 years who waitinglist follow the activities of outbound training in TSOT Group Prigen, purposive sampling is done by taking a low score scale resolution of the conflict as much as 30 teenagers who will be divided into two groups: the control group and the experiment group. Calculations made from gainscore value obtained from the pretest and posttest control group and experimental groups with nonparametric statistical Wilcoxon Signed Rank test . Based on the calculation obtained by the Sig . ( 2 tailed) is 0.001 < 0.05 , the obtained results of Ho refused and H1 accepted that there is effectiveness of outbound training model of conflict resolution in improving interpersonal conflict resolution skills in adolescent self.